Design Thinking Budget and Savings Planner Inspiration of the Hadith of the Prophet - Dewi, Tryana Hafilda (Jurnal Penelitian Ilmu Ushuluddin, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in financial management. Qualitative research methods through literature study and field studies with the hadith design approach. The results and discussion of this research include good management education, inspiration for the example of the Prophet. in saving, and the Budget and Saving Planner. This research concludes that the hadith of the Prophet. has inspirational messages in raising awareness of saving with the presence of the Budget and Savings Planner book through innovative ideas with continuous testing appropriately to create Indonesians who like to save and increase awareness of saving for the Indonesian people.